PENGARUH FRAMING DAN KEMAMPUAN NUMERIK TERHADAP KEPUTUSAN INVESTASI - Pasek, Gede Widiadnyana; Widanaputra, Anak Agung Gede Putu; Ratnasari, Maria Mediatrix (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aims to determine the difference between the investment decisions of low and high numerical ability and given treatment that is not given framing with framing treatment. The study population was Student Master in management. The study design is a 2 X 2 factorial design to data collection used questionnaires in the form of a case. Once the experiment ends the data were analyzed with ANOVA two ways. The results showed (1) there is a difference between the given decision is not given framing with framing, (2) there are differences in decision making between the subjects with a high numerical ability and a low numerical abilities. From the results concluded that the framing and numerical ability to give effect to the investment decision
Keywords: Framing, Numerical ability, Investment Decision.